Surgical Anatomy of the Rectus-Sparing Approach for Periacetabular Osteotomy: A Cadaveric Study. Issue 2 (April 2021) - Kalhor, Morteza; Gharehdaghi, Jaber; Leunig, Michael; Ahmadloo, Javad; Collado Gastalver, Diego; Ganz, Reinhold
Abstract : Background: The Bernese periacetabular osteotomy (PAO) is a widely used technique for the management of acetabular dysplasia and other hip deformities in adolescents and young adults. Originally, the approach was described with a release of both origins of the rectus femoris muscle1 . In the more recently described rectus-sparing approach, both heads remain attached2, 3 . It has been proposed that this modification may decrease pain, ease postoperative rehabilitation, and avoid heterotopic ossifications, without limitations of the surgical overview. Description: Both the original and the rectus-sparing approach are modifications of the Smith-Petersen approach. The skin incision and further dissection remain identical in both approaches for the protection of the lateral femoral cutaneous nerve, the osteotomy of the anterior superior iliac spine (or takedown of the inguinal ligament), the exposure of the iliac fossa, and the medial retraction of the abdominal and iliopsoas muscles. In both variants, the further dissection traverses the iliopectineal bursa. In contrast to the original approach, in which the rectus muscle becomes part of the medial flap after releasing both heads, the rectus-sparing approach involves the undetached rectus muscle becoming part of the lateral flap while the medial flap includes the sartorius and iliacus-iliocapsularis muscles. The anterior capsule and deep structures can be accessed through the interval between the rectus femoris and iliopsoas muscles or lateral to the rectus muscle. The remaining surgical steps are again similar in both techniques. According to preference, the surgeon starts with the pubic osteotomy or with the ischial cut first, the latter avoiding additional bleeding from the pubic osteotomy. For the ischial osteotomy, the bone is accessed by making an anteroposterior tunnel between the medial capsule and the iliopsoas tendon anteriorly and between the medial capsule and the obturator externus muscle posteriorly. While the ischial osteotomy is an incomplete separation, the pubic osteotomy is a complete separation. It sections the superior pubic ramus medial to the iliopectineal eminence, in a somewhat oblique fashion. The third and fourth cuts are made in the iliac bone in such a way as to keep the posterior column intact. By connecting the posterior iliac and ischial cuts as the last osteotomy step, the acetabulum is freed and repositioned as needed. The aim of our cadaver dissection is primarily to describe part of the rectus-sparing approach and to test this modification for eventual disadvantages over the classic approach. The remaining steps of the procedure correspond to the approach as described earlier1, 4, appreciating that several modifications of the procedure are in use. Alternatives: Nonsurgical treatment may be an alternative in borderline dysplasia; however, it needs to be reconsidered and eventually changed to surgical treatment when symptoms persist or come back. Other current techniques for surgical treatment of adolescent and adult hip dysplasia include triple and rotational or spherical osteotomies5 -7 . Rationale: The Bernese PAO is performed through a single incision. All cuts are performed from the inner side of the pelvis, avoiding interference with the vascularity of the acetabular and periacetabular bone, which mainly comes from the outside of the pelvis8 . The procedure needs minimal hardware for fixation, and partial weight-bearing can be allowed. The PAO provides a wide range of acetabular reorientation options. Wide capsulotomy and intra-articular procedures are possible, as well as additional femoral corrections. Childbirth via natural delivery is possible even after bilateral PAO9 . Nerve injuries can be guarded against with careful surgical execution of the osteotomies4 .